EVALUATING THE ROLE OF THE BALANCED SCORECARD IN ENHANCING HEALTHCARE ORGANIZATIONAL PERFORMANCE: A SYSTEMATIC REVIEW - Mohammad Raffy yusmar (Global Journal of Health Administration, 2025)
Objective: The publication explores the use of the Balanced Scorecard (BSC) in healthcare, focusing on its benefits, challenges, and recent adaptations for sustainability, community engagement, and crisis management. It aims to provide recommendations to help healthcare organizations effectively use the BSC to improve their performance and service quality. Methods: This study conducts a systematic review of scientific publications on the Balanced Scorecard within the healthcare sector using the PubMed database. The search strategy employed the following keywords: ("Balanced Scorecard"[Title/Abstract] OR "Balanced Scorecard"[MeSH Terms]) AND ("Healthcare"[Title/Abstract] OR "Health Care"[MeSH Terms] OR "Hospitals"[MeSH Terms]) AND   ("Effect"[Title/Abstract] OR "Impact"[Title/Abstract] OR "Outcome"[Title/Abstract] OR "Evaluation"[Title/Abstract]). The search was limited to articles published within the last 10 years. Results: The initial search yielded 30 studies, of which 15 met the inclusion criteria after screening and were included in this systematic review. These studies span diverse healthcare settings such as hospitals, emergency departments, healthcare centers, and public health organizations, highlighting the global relevance of the Balanced Scorecard in healthcare. Conclusion: This study shows that the Balanced Scorecard  (BSC)  is  widely  used  across  global healthcare settings and effectively integrates financial and non-financial measures to improve performance, engagement, and decision-making. Its adaptability makes it a valuable tool for ongoing healthcare improvement and sustainable delivery worldwide.